The 18.6-year nodal tidal cycle and the bi-decadal precipitation oscillation over the plains to the east of subtropical Andes, South America - Agosta Scarel, Eduardo Andres (2014)
This work shows statistical evidence for lunar nodal cycle influence on the low-frequency summer rainfall variability over the plains to the east of subtropical Andes, in South America, through long-term sea surface temperature (SST) variations induced by the nodal amplitude of diurnal tides over southwestern South Atlantic (SWSA). In years of strong (weak) diurnal tides, tide-induced diapycnal mixing makes SST cooler (warmer) together with low (high) air pressures in the surroundings of the Malvinas/Falklands Islands in the SWSA, possibly through mean tropospheric baroclinicity variations. As the low-level tropospheric circulation anomalies directly affect the interannual summer rainfall variability, such an influence can be extended to the bi-decadal variability present in the summer rainfall owing to the nodal modulation effect observed in the tropospheric circulation. The identification of the nodal periodicity in the summer rainfall variability is statistically robust.